Strategi Pemasaran Bank di Semarang: Pendekatan Studi Pustaka - Amin, Mochamad Tilawatil (Jurnal Ekonomi, Bisnis dan Manajemen, 2025)
This article explores the marketing strategies implemented by various banking institutions in Semarang City through a literature review approach. The study aims to analyze marketing practices that focus on service quality, customer satisfaction, community-based engagement, and Sharia-compliant innovation. The findings indicate that banks such as PT. BPR BKK Kota Semarang, Bank Jateng, BPR Arto Moro, and Bank Syariah Mitra Harmoni employ various strategies to reach diverse market segments by enhancing service quality, strengthening community ties, and integrating local cultural and Islamic values into their financial products. These strategies have been proven to improve customer satisfaction and loyalty. This study provides both theoretical and practical contributions to the development of locally responsive bank marketing strategies aligned with social and cultural needs.